Affective reactions influence investment decisions: Evidence from a laboratory experiment with taxation - Katharina Schüßler; Johannes Hewig; Dirk Kiesewetter; Martin Fochmann (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
We investigate the effect of taxation on gains and losses on the investment behavior of investors. Based on the insights of both economic research on the influence of taxation on investment behavior and psychological concepts dealing with the descriptive decision behavior of investors we expect investors to react to taxation of investment alternatives they face with behavioral and affective changes. By conducting a laboratory experiment with a total of 72 participants based on the experimental design of Fochmann, Kiesewetter, and Sadrieh (2012) that allows to quantify the reactions of investors to taxation on gains and loss deduction independent of their individual risk preferences and additionally measuring the affective reactions of our participants, we explore the role of affect in the relation of taxation and decision making. Hence, we are able to show that affective reactions to the taxation situations, in particular the perceived valence of these situations, influence the change in behavior of investors when confronted with taxation on gains and limited loss deduction.
Keywords: C91; D14; H24; 330; decision making; risk taking behavior; behavioral taxation; distorting taxation; affect; valence